2015
DOI: 10.18632/oncotarget.4296
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted role of TREX2 in the skin defense against UV-induced skin carcinogenesis

Abstract: TREX2 is a 3′-DNA exonuclease specifically expressed in keratinocytes. Here, we investigated the relevance and mechanisms of TREX2 in ultraviolet (UV)-induced skin carcinogenesis. TREX2 expression was up-regulated by chronic UV exposure whereas it was de-regulated or lost in human squamous cell carcinomas (SCCs). Moreover, we identified SNPs in the TREX2 gene that were more frequent in patients with head and neck SCCs than in healthy individuals. In mice, TREX2 deficiency led to enhanced susceptibility to UVB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 59 publications
4
34
0
Order By: Relevance
“…This is in agreement with previous data demonstrating that TREX2 interacts with phosphorylated histone H2AX (γH2AX) (Manils et al, 2015), a critical player in both DNA repair and DNA degradation (Baritaud et al, 2010;Lu et al, 2006). Additionally, it has been shown that TREX2 can modulate DNA double-strand break repair (Bennardo et al, 2009) and replication fork stalling following DNA damage (Hu et al, 2013).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in agreement with previous data demonstrating that TREX2 interacts with phosphorylated histone H2AX (γH2AX) (Manils et al, 2015), a critical player in both DNA repair and DNA degradation (Baritaud et al, 2010;Lu et al, 2006). Additionally, it has been shown that TREX2 can modulate DNA double-strand break repair (Bennardo et al, 2009) and replication fork stalling following DNA damage (Hu et al, 2013).…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Deficiencies in these nucleases lead to the accumulation of self DNA, which triggers a strong type I interferon signature and results in autoinflammatory diseases (Gall et al, 2012;Grieves et al, 2015;Yoshida et al, 2005). In contrast, TREX2 deficiency dampened the inflammatory response in a IMQ-induced psoriasis-like mouse model, and in response to ultraviolet-B radiation (Manils et al, 2015). These data support a non-redundant positive regulatory role for this exonuclease in skin inflammatory responses under stress conditions.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 63%
See 1 more Smart Citation
“…However, TREX2knockout mice are more susceptible to skin carcinogenesis induced by UVB radiation exposure or application of 7, 12-dimethylbenz[a]anthracene, a DNAdamaging carcinogen. These findings correlate with a decrease in keratinocyte apoptosis and a decrease in inflammatory responses induced after DNA damage in TREX2-deficient mice (Manils et al, 2015;Parra et al, 2009). These studies indicate that TREX2 can degrade damaged nucleic DNA, leading to keratinocyte cell death and activation of an inflammatory immune response that normally clears damaged cells and prevents the development of cutaneous tumors.…”
Section: Trex2supporting
confidence: 53%
“…Knowing that TREX2 mRNA is upregulated significantly in psoriatic lesions (Li et al, 2014) and that TREX2 can lead to the induction of mediators of innate inflammatory responses, such as tumor necrosis factor-a, inducible nitric oxide synthase, IL-6, and IFN-g (Manils et al, 2015), Manils et al (2016) examined the role of TREX2 in the pathogenesis of psoriasis. Their studies found that loss of TREX2 abrogated the inflammation that is normally induced in two acute murine models of psoriasis, the imiquimod and recombinant IL-23 models.…”
Section: Trex2mentioning
confidence: 99%